Relationship between off-season changes in power and in-season changes in skating speed in young ice hockey players - Haukali, E.; Tjelta, L. I. (International Journal of Applied Sports Sciences, 2016)
The purpose of this study was to examine whether there exists a correlation between changes in off-season power and changes in in-season skating performance among young ice hockey players. Eighteen elite male players (15.8 ± 0.9) completed on-ice and off-ice performance tests on three separate occasions during a season. Forward and backward skating speed, on-ice agility test, 36 m sprint running performance, broad jump and countermovement jump (CMJ) were included. Off-season improvements in 36 m sprint running performance (r = 0.57, P= 0.02) and changes in broad jump (r = -0.48, P= 0.04) where significantly correlated with in-season improvements in forward skating speed. However, off-season changes in 36 m sprint running performance and jump ability were not significantly correlated with in-season improvements in backward skating speed or agility. These results suggest that an off-season training program that includes sprints and horizontal jumping exercises may have a positive effect on hockey players` linear skating speed.